2021
DOI: 10.29244/j.agromet.35.2.116-124
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Garlic Farming on Climate Change and Variability in Lombok

Abstract: Climate change impact in Indonesia is generally characterized by changes in daily temperature, rainfall patterns, and sea level rise. These changes mainly influence agricultural practices for various crops, including garlic (Alium sativum L.).  Current knowledge on climate vulnerability related to agricultural impact in Indonesia is limited. This study aims to identify the level of vulnerability of garlic farmer households to climate change and provide recommendations for adaptation activities for garlic farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Nevertheless, it is also known that some garlic varieties have phenotypic plasticity in response to different environments (Volk & Stern, 2009;Kizil & Khawar, 2017;Sánchez-Virosta et al, 2021). Some studies have revealed that different agronomic responses exist in garlic varieties under various environmental factors e.g., photoperiod and temperature (Atif et al, 2019;Mathew et al, 2011), water stress (Sánchez-Virosta & Sánchez-Gómez, 2019), different fertilizer levels (Shree et al, 2014), climatic changes (Tchórzewska et al, 2017;Mahmudah et al, 2021), and planting time (Alsup-Egbers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is also known that some garlic varieties have phenotypic plasticity in response to different environments (Volk & Stern, 2009;Kizil & Khawar, 2017;Sánchez-Virosta et al, 2021). Some studies have revealed that different agronomic responses exist in garlic varieties under various environmental factors e.g., photoperiod and temperature (Atif et al, 2019;Mathew et al, 2011), water stress (Sánchez-Virosta & Sánchez-Gómez, 2019), different fertilizer levels (Shree et al, 2014), climatic changes (Tchórzewska et al, 2017;Mahmudah et al, 2021), and planting time (Alsup-Egbers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hahn et al, (2009) developed LVI (Livelihood Vulnerability Index) as a versatile approach in vulnerability assessment based on indicators that can be modified for broader context. The results of LVI assessment could provide specific information regarding demographics, social, or economics that contributed to climate change vulnerability for local government to build resilience and minimize climate change impact in the community (Ali and Hossen, 2022;Mahmudah et al, 2021;Minh et al, 2020). Apart from LVI, another method in vulnerability assessment was developed by the Ministry of Environment and Forestry, Republic of Indonesia, in 2015.…”
Section: Introductionmentioning
confidence: 99%